2014
DOI: 10.1038/leu.2014.144
|View full text |Cite
|
Sign up to set email alerts
|

PRPF8 defects cause missplicing in myeloid malignancies

Abstract: Mutations of spliceosome components are common in myeloid neoplasms. One of the affected genes, PRPF8, encodes the most evolutionarily conserved spliceosomal protein. We identified either recurrent somatic PRPF8 mutations or hemizygous deletions in 15/447 and 24/450 cases, respectively. 50% of PRPF8 mutant and del(17p) cases were found in AML and conveyed poor prognosis. PRPF8 defects correlated with increased myeloblasts and ring sideroblasts in cases without SF3B1 mutations. Knockdown of PRPF8 in K562 and CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 51 publications
(64 reference statements)
1
63
0
Order By: Relevance
“…Notably, 50% of PRPF8 mutant and deletion of chromosome 17p cases were found in AML. Survival analysis confirmed that PRPF8 was associated with poor prognosis (91).…”
Section: Abnormally Spliced (As) Mrnas In Amlmentioning
confidence: 54%
See 1 more Smart Citation
“…Notably, 50% of PRPF8 mutant and deletion of chromosome 17p cases were found in AML. Survival analysis confirmed that PRPF8 was associated with poor prognosis (91).…”
Section: Abnormally Spliced (As) Mrnas In Amlmentioning
confidence: 54%
“…Combing these evidences, we could imply that PRPF8 is required for haematopoietic development and defective PRPF8 could be conducive to myeloid malignancies. Indeed, KurtovicKozaric and coworkers identified either recurrent somatic PRPF8 mutations or hemizygous deletions in 3.3% (15 out of 447 cases) and 5.3% (24 out of 450 cases) of myeloid neoplasms, respectively (91). Notably, 50% of PRPF8 mutant and deletion of chromosome 17p cases were found in AML.…”
Section: Abnormally Spliced (As) Mrnas In Amlmentioning
confidence: 99%
“…1) [4]. Along with these, multiple loss-of-function mutations [5][6][7][8][9][10][11][12], and recurrent activated/gain-of-function mutations [13][14][15][16] are likely to be the promising candidates for future development of novel therapy by inhibitory compounds (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mutations in PRPF8 have been identified in MDS and AML patients where decreased PRPF8 expression is associated with increased exon skipping [53], possibly due to a splicing proofreading defect [53]. While DDX41 R525H is associated with reduced binding to SF3B1 and PRPF8, DDX41 mutations have not been reported in association with MDS with ring sideroblasts that is often characteristic of mutations in SF3B1 [50] and PRPF8 [53].…”
Section: Ddx41 In Mrna Splicingmentioning
confidence: 99%